Implementasi Kurikulum 2013 Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Dalam Membentuk Karakter Siswa Sdit Sabilul Huda Kota Cirebon - FNU Badruzzaman (Oasis : Jurnal Ilmiah Kajian Islam, 2019)
This research aims to study the implementation of the curriculum of 2013 on subjects of Islamic religious education and Manners in shaping the character of the Students Sabilul Huda SDIT Cirebonwhich include: planning, implementation and evaluation of the learning of Islamic education and Manners in the curriculum in 2013 SDIT Sabilul Huda city of Cirebon. In this study also discussed the process of the formation of character students SDIT Sabilul Huda city of Cirebon is a realization of curriculum implementation of 2013.This type of research is a reseach field (field research) research is done directly in the SDIT Sabilul Huda Cirebon City school year 2017/2018. As for that being the subject of this research is the students and teachers of Islamic religious education in the SDIT Sabilul Huda city of Cirebon the year 2018. Engineering data collection using the way of observation, interview and documentation. Conclusion of this research is the first, PAI and learning Manners by implementing curriculum 2013 has been running well. Secondly, the formation of character students SDIT Sabilul Huda city of Cirebon was already well underway through the activities that reflect the creation of the character of students. Involve students directly in the religious and social kegiatana. Third, the obstacles encountered in the implementation of school curriculum related issues 2013 availability book teachers and students, government regulation that is often fickle, administrative Character learning that complicated,and assessment process that is time-consuming. Penelitian ini bertujuan untuk mengkaji Implementasi Kurikulum 2013 pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti dalam Membentuk Karakter Siswa SDIT Sabilul Huda Kota Cirebon yang meliputi: Perencanaan, pelaksanaan dan evaluasi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti pada Kurikulum 2013 di SDIT Sabilul Huda Kota Cirebon. Dalam penelitian ini juga dibahas proses pembentukan karakter siswa SDIT Sabilul Huda Kota Cirebon yang merupakan realisasi dari penerapan kurikulum 2013.Jenis penelitian ini adalah field reseach (penelitian lapangan) penelitian ini dilakukan langsung di SDIT Sabilul Huda Kota Cirebon tahun ajaran 2017/2018. Adapun yang menjadi subjek penelitian ini adalah siswa dan guru Pendidikan Agama Islam di SDIT Sabilul Huda Kota Cirebontahun 2018. Teknik pengumpulan data menggunakan cara observasi, wawancara dan dokumentasi.Kesimpulan penelitian ini adalah pertama, proses pembelajaran PAI dan Budi Pekertisudah berjalan cukup baik, Kedua, pembentukan karakter siswa SDIT Sabilul Huda Kota Cirebon sudah berjalan dengan baik yaitu melalui kegiatan-kegiatan yang mencerminkan pembentukan karakter siswa. Melibatkan siswa secara langsung dalam kegiatan keagamaan dan sosial. Ketiga, hambatan yang dihadapi sekolah dalam pelaksanaan kurikulum 2013 terkait masalah ketersediaan buku guru dan siswa, regulasi pemerintah yang sering berubah-ubah, administrasi pembelajaran yang rumit,dan proses penilaian yang menyita waktu.